RISK FACTORS FOR SURGICAL SITE INFECTION FOLLOWING CESAREAN SECTION - AYESHA, .; NASREEN, .; SHAZIA, .; JAWARIA, .; RAFIQUE, H (Biological and Clinical Sciences Research Journal, 2024)
Surgical site infections (SSIs) following cesarean sections (CS) are significant contributors to maternal morbidity and healthcare burdens worldwide. Despite adherence to preoperative guidelines, certain risk factors remain associated with increased SSI rates. Identifying and addressing these factors is essential for improving patient outcomes. Objective: To identify and evaluate the risk factors associated with surgical site infection (SSI) following cesarean section (CS) based on the World Health Organization’s recommended preoperative measures in a tertiary care hospital in Mirpur, AJ & K. Methods: A prospective cohort study was conducted from January 2022 to December 2023 at a tertiary care hospital in Mirpur, AJ&K. A total of 1,500 patients undergoing cesarean sections were enrolled and followed for 30 days post-surgery to monitor for the occurrence of SSI. Data on potential risk factors, such as body mass index (BMI), diabetes, hypertension, preoperative antibiotic use, duration of surgery, type of cesarean section (elective vs. emergency), anemia, and personal hygiene practices, were collected at baseline. The primary outcome was the incidence of SSI, diagnosed according to the Centers for Disease Control and Prevention (CDC) criteria. Risk factors were compared between patients who developed SSI (cases) and those who did not (controls). Statistical analyses, including Chi-squared and Fisher’s Exact tests, were performed to identify significant risk factors. Multivariate logistic regression was used to control for confounding factors. Results: Out of the 1,500 patients, 18% (n=270) developed SSI within 30 days of surgery. Significant risk factors for SSI included obesity (BMI >30), which increased the odds of SSI by 2.5 times (p=0.001); prolonged hospital stay of more than 5 days, associated with a 1.8-fold increase in SSI risk (p=0.004); emergency cesarean sections, which raised the risk by 2.1 times compared to elective procedures (p=0.002); and anemia (hemoglobin <10 g/dL), which increased SSI risk by 1.9 times (p=0.005). Poor personal hygiene practices were also significantly associated with a higher incidence of SSI (p=0.003). On the other hand, the use of preoperative prophylactic antibiotics was protective, reducing the incidence of SSI by 3.2-fold (p=0.0001). No significant associations were observed between the duration of surgery (p=0.21) or patient age (p=0.15) and the occurrence of SSI. Conclusions: This prospective cohort study identified obesity, prolonged hospital stay, emergency cesarean section, anemia, and personal hygiene practices as significant risk factors for the development of SSI following cesarean section, consistent with the World Health Organization’s preoperative guidelines. The use of preoperative prophylactic antibiotics was shown to be an effective intervention in reducing SSI risk. These findings underscore the importance of targeted preventive measures, including weight management, prompt hospital discharge, enhanced personal hygiene education, and the routine use of prophylactic antibiotics, in reducing the burden of SSIs in cesarean sections.